Improving adolescent knowledge and attitude toward the intergenerational cycle of undernutrition through audiovisual education: findings from RESEPIN study in Yogyakarta, Indonesia - Tri Siswati; Yustiana Olfah; Heru Subaris Kasjono; Bunga Astria Paramashanti (Wolters Kluwer Medknow Publications, 2022)
Background: Adolescent health and nutrition contribute to the intergenerational cycle of undernutrition. Objectives: The aim of this study is to examine the effect of audiovisual education on adolescent knowledge and attitude toward the intergenerational cycle of undernutrition. Material and Methods: A clustered quasi-experimental study with a pre-and posttest design in Kulon Progo District, Yogyakarta, Indonesia. Participants were female adolescent students enrolled in Grade 7 at two junior high schools in Sentolo (n = 120) and Kalibawang (n = 96) subdistricts. We provided six topics related to adolescent health and nutrition throughout six online meetings for the intervention and control groups. In addition, the intervention group received audiovisual education through recorded videos, whereas the control group received education through e-leaflets following the online meetings. We assessed adolescent knowledge and attitude during pre-and posttest evaluations using Google Forms. Paired t-test was performed to analyze the data. Results: Both audiovisual and e-leaflet educations increased adolescent knowledge and attitude. Adolescents who received audiovisual education had significantly higher knowledge (P = 0.046) and attitude (P = 0.034) scores than adolescents who received education through e-leaflets. Conclusions: The audiovisual education intervention improved adolescent knowledge and attitude toward the intergenerational cycle of undernutrition than using e-leaflets.